Pengaruh Kepemimpinan Transformasional, Budaya Organisasi, dan Motivasi Kerja Terhadap kinerja Karyawan (Studi Pada Industri Manufaktur Perusahaan Y di Bandung - Nurlaela, Ika; Ismail, Dr. Gurawan Dayona; Aziz, Dadan Abdul; Recky; Sudaryo, Yoyo (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
The purpose of this study is "to analyze the influence of transformational leadership, organizational culture, and work motivation on the performance of production employees at PT. Eksonindo Multi Product Industry". The study uses analysis based on quantitative data, this study attempts to identify the cause and effect relationship of the variables analyzed. Data collection is carried out through survey techniques by sending questionnaires to production employees. Determination of samples adopting the Slovin method with an inaccuracy rate of 10%, with a sample of 22 employees. The variables in this study consist of independent variables "(transformational leadership x1, organizational culture x2, and work motivation x3)" and dependent variables "(employee performance y)". Data analysis through several regression techniques using SPSS tools to test the hypothesis in this study. The findings of the study are expected to provide a complete description of what aspects influence "employee performance" of production, as well as provide practical recommendations to company management in its efforts to improve organizational performance.